2017
DOI: 10.1371/journal.pone.0178619
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib attenuates cardiac fibrosis by inhibiting platelet-derived growth factor receptors activation in isoproterenol induced model

Abstract: Cardiac fibrosis is a significant global health problem with limited treatment choices. Although previous studies have shown that imatinib (IMA) inhibited cardiac fibrosis, the anti-fibrotic mechanisms have not been clearly uncovered. The aim of this study is to evaluate whether IMA attenuates cardiac fibrosis by inhibiting platelet-derived growth factor receptors (PDGFR) on isoproterenol (ISO)-induced mice. Adult male C57BL/6 mice were treated with vehicle or ISO ± IMA for one week. After echocardiography exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…Isoproterenol stimulation to create myocardial injury. To examine cardiac tolerance in a stress environment, we used the isoproterenol-induced myocardial injury model as previously described [11][12][13][14]. Isoproterenol hydrochloride, a synthetic non-selective β-adrenergic agonist, was dissolved in physiological saline.…”
Section: Analysis Of Cardiac Function and Histological Changementioning
confidence: 99%
“…Isoproterenol stimulation to create myocardial injury. To examine cardiac tolerance in a stress environment, we used the isoproterenol-induced myocardial injury model as previously described [11][12][13][14]. Isoproterenol hydrochloride, a synthetic non-selective β-adrenergic agonist, was dissolved in physiological saline.…”
Section: Analysis Of Cardiac Function and Histological Changementioning
confidence: 99%
“…In our previous study [ 22 ], we found that the PDGF-A expression was significantly increased in the ISO group model heart, and the kinase activity of PDGFRα also was enhanced in the heart of the cardiac fibrosis model. PDGF-AA (activated form of PDGF-A) treatment could activate the fibroblasts by binding and activating PDGFRα [ 25 ].…”
Section: Resultsmentioning
confidence: 94%
“…In our previous study [ 22 ], we successfully constructed a mice model of cardiac fibrosis using ISO. To assess the activity changes of c-Kit in a cardiac fibrosis model, we tested the phosphorylation state of c-Kit (p-Kit: Tyr719) in the hearts of cardiac fibrosis model mice by western blotting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Col‐I is produced mainly by fibroblasts, it plays an important role in homeostasis in normal tissue and cell growth, invasion, and metastasis in cancer tissue (Kong et al, ). α‐SMA is overexpressed in local fibroblasts (Wang et al, ). These results demonstrated that RASSF1‐AS1 exacerbated cardiac fibroblast activation and inflammation in vitro, but RASSF1‐AS1‐del could not.…”
Section: Resultsmentioning
confidence: 99%